Pathological features of early pregnancy disorders in women living at high altitude in KSA - Khalid Nafie, MD; Abdulkarim Hasan, MD; Wesam K. Alshakhrit, MD; Amal Ismail, MD; Osama Abbadi, MD (Journal of Taibah University Medical Sciences, 2023)
الملخص: أهداف البحث: يعتقد بأن عملية الحمل تمثل إحدى التحديات التي تواجهها النساء اللاتي يقطن الأماكن شديدة الارتفاع عن سطح البحر، وذلك نظرا لصعوبة التأقلم مع معضلة نقص الأكسجين. من خلال هذا البحث تم دراسة مجموعة من الخصائص المرضية النسيجية (الباثولوجية) لبعض اضطرابات الحمل التي تتضمن فقدان الحمل (الإجهاض) بين النساء الحوامل اللائي يقطن منطقة مرتفعة عن سطح البحر بحوالي 2200 متر بالمملكة العربية السعودية. طرق البحث: دراسة مقطعية تم خلالها جمع البيانات بأثر رجعي من مستشفى واحد واقع في منطقة مرتفعة وذلك خلال عامي 2018-2020 . النتائج: أسفرت النتائج عن أن نسبة تقدر بحوالي 55% من النساء اللاتي حدث عندهن حمل غير مكتمل (إجهاض أو حمل العنقودي أو حمل خارج الرحم) كانت أعارهن تقل عن 35 عامًا. وقد دلت الإحصائية على أن نسبة الحمل خارج الرحم وصلت إلى 6.8% من تلك الاضطرابات. وقد بلغ معدل الإجهاض 19% من إجمالي عدد حالات الحمل التي تمت دراستها الاستنتاجات: توصي الدراسة الباحثين باستكمال وتواصل الدراسات في هذا الشأن وأن تشتمل دراساتهم المستقبلية على عدد أكبر من السيدات الحوامل في تلك المناطق شديدة الارتفاع عن سطح الأرض مستعينين بالتحليلات الجينية وغيرها من الوسائل التي تساعد على التوصل إلى نتائج أكثر دقة والتعرف على الأسباب وطرق الوقاية من تلك الاضطرابات، إضافة إلى الحاجة إلى المزيد من الدراسات المماثلة بمناطق تقع على مستوى سطح البحر. Abstract: Objectives: Pregnancy at high altitudes is relatively challenging because of hypobaric hypoxia, which is associated with a smaller uterine artery diameter and diminished blood flow. Here, we investigated the histopathological characteristics of early pregnancy disorders among pregnant women living in a high-altitude region (approximately 2200 m above sea level). Methods: This cross-sectional study used retrospective data collection from a single tertiary hospital in a high-altitude region in KSA. Age and histopathology were analyzed in 495 women diagnosed with early pregnancy disorders (mainly miscarriage) in 2018–2020. Results: Approximately one-fifth of pregnancies in this high-altitude region were lost before 24 weeks’ gestation, whereas 1150/6044 experienced miscarriage; 495 samples from those participants were sent for histopathological analysis. A total of 269 (54.34%) patients were younger than 35 years. Missed miscarriages accounted for 49.3% of miscarriages, followed by inevitable miscarriages (34.2%), which had a relatively higher frequency among mothers older than 35 years. The correlation between age and inevitable miscarriage was significant; ectopic pregnancy was diagnosed in 6.8%, molar pregnancy was detected in 6.26%, and blighted ovum was observed in 3.4%. Conclusion: The miscarriage rate in this high-altitude region was 19% of all pregnancies. Approximately half of the affected women were in their 30s. Missed miscarriage cases were relatively high in this region. The percentage of molar pregnancy was higher than those reported in prior studies, thus suggesting a need for monitoring and genetic workup practices. Furthermore, studies involving a larger population at high altitudes will be crucial for further risk assessment in addition to national studies on women living at sea level.